Empowering Micro Small and Medium Enterprises (MSMEs) to Improve Global Economic Welfare - Bambang Irawan; Chusnul Rofiah; Asfahani Asfahani; Sufyati HS; Wahyudin Hasan (Edujavare Publishing, 2023)
In recent years, there has been a paradigm shift in understanding the role of MSMEs in the global economy. MSMEs are no longer considered local business entities but agents of change that can stimulate sustainable economic growth. This service research aims to make a real contribution to designing MSME empowerment strategies that have a broad impact, open up new opportunities, and positively affect global economic welfare. The method applied in this community service activity is community-based Research (CBR) using the forum group discussion (FGD) approach in the training and mentoring process. So, it is concluded that the empowerment of MSMEs proves its effectiveness in identifying, overcoming, and providing concrete solutions to their challenges. Involving business actors in decision-making and empowerment processes provides a solid foundation for sustainable growth. Training, mentoring, and support from the government and local communities form a supportive ecosystem in improving global economic welfare through developing MSMEs. Second, findings related to product innovation from natural resources, such as coconut and fish, show great potential in diversifying MSME businesses and opening up new opportunities in the global market.